Aktuelle Glaukomchirurgie - Hoffmann, Esther M. (Ophthalmologe, 2020)
BACKGROUND: The main goals of glaucoma treatment are to preserve the visual function and maintain as high a quality of life as possible at a cost acceptable to society. Therefore, it is crucial to carefully observe each individual patient in order to determine an individual and personalized treatment approach. MATERIAL AND METHODS: This article summarizes the advantages and disadvantages of medicinal glaucoma treatment as well as traditional methods of glaucoma surgery, based on the current state of knowledge. The article explains the various mechanisms of action of new minimally invasive procedures, introduces the methods mostly commonly used in Germany and gives recommendations for preoperative care and postoperative follow-up. RESULTS/CONCLUSION: In addition to the plethora of medicinal glaucoma treatments and classical surgical procedures, new minimally invasive treatment alternatives have become available in the past few years. The latter are an option for an earlier surgical intervention, especially in naïve or previously treated patients who appear to be unsuitable for medicinal treatment.